2017
DOI: 10.1016/j.ijid.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Biennial versus annual treatment for schistosomiasis and its impact on liver morbidity

Abstract: These findings suggest that in order to reverse moderate to severe liver fibrosis due to schistosomiasis and improve clinical outcomes, a higher clinical dosage of praziquantel (i.e., 60-80mg/kg) may be required over an extended duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Despite praziquantel therapy not being fully curative, a greater egg count reduction ratio correlated with a greater reduction in odds of most morbidities in their analyses. Olveda et al 25 also demonstrated that clinical outcomes of liver fibrosis due to schistosomiasis could be reversed over time with praziquantel treatment. Botelho et al 26 showed that schistosome infections can lead to significant, yet largely unacknowledged morbidities such as stunting and wasting, further emphasizing the need for treatment and control measures for schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite praziquantel therapy not being fully curative, a greater egg count reduction ratio correlated with a greater reduction in odds of most morbidities in their analyses. Olveda et al 25 also demonstrated that clinical outcomes of liver fibrosis due to schistosomiasis could be reversed over time with praziquantel treatment. Botelho et al 26 showed that schistosome infections can lead to significant, yet largely unacknowledged morbidities such as stunting and wasting, further emphasizing the need for treatment and control measures for schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…China has attained substantial achievements in the control of schistosomiasis japonica, with elimination now on the horizon; however, the disease remains a major public health challenge in the Philippines with high prevalence reported in several endemic areas [4, 5, 24], although the intensity of infection has been reduced following extensive MDA implementation [6]. The continuation of this high prevalence is due, in part, to the pronounced rainfall levels in the schistosome-endemic areas, promoting propagation of the Oncomelania hupensis snail intermediate hosts, and also the large number of non-human mammalian reservoirs (particularly bovines; water buffaloes and cattle) which contribute significantly to disease transmission, which makes control more challenging and difficult [5].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the estimated number of human cases dropped from 840,000 in 2004 to 54,454 by the end of 2016 [3]. In the Philippines, an estimated 580,000 individuals were reported infected as of 2010 [4], and the prevalence in a number of endemic areas remains high although the intensity of infection has dropped in recent years [5, 6]. In this era of extensive MDA and as elimination is on the horizon, more sensitive diagnostic tools for diagnosis of schistosomiasis are required.…”
Section: Introductionmentioning
confidence: 99%
“…For more than over the last three decades, the area has had active schistosomiasis control programs, including a mass drug administration (MDA) program which commenced in 2008. Free annual treatment (Praziquantel 40 mg/kg in a single dose) is delivered to all individuals aged between 5-65 years in accordance with the Department of Health Administrative Order 2007-0015, but the compliance rate varies [55]. It is worthwhile to note that the S. japonicum reinfection rate in the area is also high [56].…”
Section: Study Cohortmentioning
confidence: 99%